Impact of Work Environment upon Respiratory Tract Health Problems among Workers at Textile Industries in Baghdad City - Wissam Jabbar Qassim1 , Rajaa Ibraheem Abed2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: To evaluate the effect of the work environment on the respiratory health problem of workers inthe textile labs in Baghdad city.Methodology: The sample consisted of 100 workers working in the wool and cotton fabrics in the GeneralCompany for Textile Industries in Baghdad for the period from 3 Jan of 2017 to 20 of May 2018. Arandomized structured sample of (100) workers was selected using the probabilistic selection method. Thequestionnaire was built for the purpose of the study and the reliability of the questionnaire was verifiedthrough a pilot study and then it was presented to (10) experts to establish its credibility. (20) Items inthe questionnaire divided into three sections, namely demographic information, symptoms and signs, andfinally diseases that affect the respiratory system. The data were collected using the questionnaire methodand analyzed the data by applying statistical descriptive analysis, which includes frequency, the mean andthe computational mean, and the deductive statistical analysis, which included the Kay square test.Results:Results of the study show that the results of the study indicated that most of the workers suffer from frequentcoughs due to allergies to cotton and wool (68%) with persistent respiratory infections. The study concludedthat most of the workers suffer from persistent cough due to the sensitivity of the raw material that entersthe textile industries namely cotton and wool. Recommendation: The study recommended that furtherstudies be carried out with the possibility of carrying out an educational program for workers to reduce theoccupational hazards of the respiratory system in textile factories